Desenvolvimento de protocolo de enfermagem para prevenção de pneumonia associada à ventilação mecânica em idosos - Freitas, Fernanda Beatriz Dantas de (2022)
Introduction: Infections related to health care are considered a major care challenge worldwide, in the intensive care setting, Pneumonia Associated with Mechanical Ventilation stands out, one of the main and most common infections that occur in Intensive Care Units. Although it is considered a therapeutic challenge, its prevention can be carried out through simple and effective measures, developed mainly by the nursing team. Objective: To build and validate a protocol for the prevention of Pneumonia Associated with Mechanical Ventilation in the elderly in the light of the Theory of Functional Consequences for the Promotion of Well-Being in Elderly Adults. Method: This is a methodological research, which proposed to develop a care protocol for the prevention of ventilator-associated pneumonia in elderly patients. The research was carried out in an Intensive Care Unit in a public hospital, linked to the Unified Health System. In the 1st stage, the construction of the protocol will be based on a review of the scientific literature in line with the Theory of Functional Consequences for the Promotion of Well-Being in the Elderly. The 2nd stage will consist of the validation of the protocol content through the analysis performed by the judges (experts in the area) and semantic evaluation by nurses who make up the team of the Intensive Care Unit. Results: From the findings of the literature review, the first version of the protocol was built, containing 18 nursing interventions aimed at the prevention of Pneumonia Associated with mechanical ventilation for the elderly, after the validation of the judges and nurses, the final version of the protocol had of 14 interventions, which considered changes related to the aging process. Discussion: With the nursing actions/interventions listed in this protocol, care will be more directed towards anatomical, physiological, immunological and structural changes, in addition to a greater focus on risk factors that affect the elderly, especially with regard to the elderly who need intensive care, providing care directed to the particularities of this public. Conclusion: In this way, the creation of the protocol for the Prevention of Pneumonia Associated with mechanical ventilation for the elderly, will be able to provide a more qualified and safe assistance to these individuals, in addition to reducing the morbidity and mortality rates in the Intensive Care Units in this age group, with consequent reduction of length of stay in the service and reduction of hospital expenses.